Analysis of the Arbovirosis Potential Occurrence in Dobrogea, Romania - Maftei Carmen; Barbulescu Alina; Rugina Sorin; Nastac Cristian Dorin; Dumitru Magdalena Irina (MDPI, 2021)
Climate change creates new challenges for preventing and protecting human health against different diseases that could appear and propagate. The Aedes albopictus mosquito species is an important vector for different diseases like dengue fever or zika. Although this species is not “indigenous” in Europe, its presence is noticed in many countries on the continent. The Ae. albopictus establishment is conditioned by the species’ characteristics and environmental factors. To assess the possible spread of Ae. albopictus in the Dobrogea region (situated in the Southeast of Romania), we conducted the following analysis: (1) Investigation of the current distribution and climatic factors favoring Ae. albopictus’ establishment in Europe; (2) Analysis of climate dynamics in Dobrogea in terms of the parameters identified at stage (1); (3) Testing the hypothesis that the climate from Dobrogea favors Ae. albopictus’ establishment in the region; (4) Building a Geographic Information System (GIS)-based model of the potential geographic distribution of Ae. albopictus in Dobrogea. Results show that the climate of Dobrogea favors the apparition of the investigated species and its proliferation.
Keywords: hydro-climate factors; statistical analysis; GIS analysis; arbovirosis